Isaiah - Penner, Ken, (Septuagint Commentary Series., 2020)
"This work consists of an introduction, transcription, translation, and commentary to the Greek translation of Isaiah in the Codex Sinaiticus. It comments on the Greek language in its context, especially on how the Greek language is stretched beyond its normal range of function. It addresses the peculiarities of Codex Sinaiticus, including its history, scribes, divisions, and orthography. In line with the aims of the Brill Septuagint Commentary Series, it mainly discusses not how the text was produced, but how it was read"--